Shaṭṭārīyah Tradition on West Java: the Case of Pamijahan - Tommy Christomy (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
The Shattariyyah tradition in Pamijahan, which this article deals with, is a good example of the dynamics of sufi tradition in Java, which can be seen from their reception on narrative of the Sufi master (silsilah). The discussion of this article will elaborate the silsilah of Shattariyyah in Pamijahan and its implication to their followers. It is evident that until now there is no adequate information regarding Shattariyyah tradition in West Java, particularly Pamijahan, which had been a famous center of Shattariyyah in Java since its the early period. Describing this issue, it is hoped that article can come to the description of general background of Shattariyyah tradition in Indonesia.DOI: 10.15408/sdi.v8i2.688